Single step fabrication of polymer/silicate porous composite membranes via water-glass induced phase inversion. Issue 9 (13th June 2019) - Kollia, Eleni; Mastrotheodoros, George; Kosma, Vasiliki; Beltsios, Konstantinos G.
ABSTRACT: Water-glass, a low-cost silica precursor solution, is used to produce mostly skinned, polymer–silicate composite membranes with a porous bulk. We explore primarily Nylon 6-10/formic acid dopes where the polymer solvent is an acid, and polysulfone/DMF dope as an example of a polymer dope based on a non-acidic water-miscible solvent. Elemental distribution of silicon in cross sections suggests compositional uniformity of the formed membranes with in some cases 20 wt. % of silicate load. Membranes formed can be used either as separation media or as precursors for compact polymers reinforced with silicate particles. Graphical Abstract: